Niche characteristics and dynamics of dominant species in arbor layer of 4hm2Pinus tabuliformis-Quercus wutaishansea mixed forest in Lingkong Mountain - Ni, Lu; Guo, Donggang; Zhang, Quanxi; Li, Yan; Hu, Xiuqin; Li, Yun; Feng, Senxia (Frontiers in Ecology and Evolution, 2024)
In order to study the niche characteristics and dynamic changes of the dominant species in the arbor layer of the 4hm 2 Pinus tabuliformis-Quercus wutaishansea mixed forest sample plot in Lingkong Mountain,and to gain a better understanding of the competition and coexistence among species in the sample plot, this study was conducted based on a typical community investigation. Four indices of important value, niche width, niche overlap, and niche similarity were chosen to calculate and analyze the niche characteristics and examine dynamic changes over a period of 10 years from 2011 to 2021. The results showed that: (1) In 2021, the important values for Quercus wutaishansea and Pinus tabuliformis were 19.906 and 13.906, respectively.The niche widths were 0.962 and 0.555, which showed difference compared to those in 2011. Both were much larger than other species, indicating that they occupied an absolutely dominant position in the community. ( 2) The mean values of niche overlap and similarity of dominant species in the arbor layer of the Lingkong Mountain sample plot have both increased over the past 10 years. Additionally, the species pairs with the highest overlap and similarity values have changed, suggesting an intensification of competition among these species.